2011
DOI: 10.1007/s11199-011-0106-2
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Issues of Gender in Stalking Research

Abstract: Stalking research has increased substantially in the past 20 years. This special issue is intended to contribute to this literature by using gender as a focus point in 1) applying new theoretical perspectives that incorporate the role of gender to the study of stalking perpetration (Davis et al. 2010; Duntley and Buss 2010), 2) addressing divergent findings regarding gender in experiences of victims (Sheridan and Lyndon 2010) and perpetrators (Thompson et al. 2010), and 3) furthering the study of how gender in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 81 publications
2
17
0
Order By: Relevance
“…Scott et al (2018) found that stalking by a male against a female is considered more serious and is more likely to result in fear of violence than the same behaviors by a woman against a man. This supports previous findings (e.g., Cass and Mallicoat, 2015;Podaná and Imríšková, 2016;Sheridan and Scott, 2010) and statistics that report more prosecutions for female targets than male (Lyndon et al, 2012), but contradicts other findings that suggest there is no gender difference (e.g., Sheridan, North, and Scott, 2014;Strand and McEwan, 2012). As Madriz (1997) has identified that women fear black men, it is important to examine the extent to which attributions of stalking are due to gender, race, or a combination.…”
Section: Perpetrator-target Gendersupporting
confidence: 91%
“…Scott et al (2018) found that stalking by a male against a female is considered more serious and is more likely to result in fear of violence than the same behaviors by a woman against a man. This supports previous findings (e.g., Cass and Mallicoat, 2015;Podaná and Imríšková, 2016;Sheridan and Scott, 2010) and statistics that report more prosecutions for female targets than male (Lyndon et al, 2012), but contradicts other findings that suggest there is no gender difference (e.g., Sheridan, North, and Scott, 2014;Strand and McEwan, 2012). As Madriz (1997) has identified that women fear black men, it is important to examine the extent to which attributions of stalking are due to gender, race, or a combination.…”
Section: Perpetrator-target Gendersupporting
confidence: 91%
“…However, stalking as a legislative term applies to a multitude of activities, many of which are harmless under normal conditions, and which are not easily defined in legal terms (Sheridan & Davies, 2001;Lyndon, Sinclair, MacArthur, Fay, Ratajack & Collier, 2012). In fact, it may be difficult to draw a line between behaviors that constitute romantic courtship and harassment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, stalking is often perceived as a gendered phenomenon, invoking different sets of assumptions and expectations regarding male and female perpetrators and victims (Lyndon et al, 2012). Despite these difficulties, stalking generally refers to persistent harassment in which one person repeatedly attempts to impose unwanted communication and/or contact on another (Mullen, Pathe, & Purcell, 2001).…”
Section: Introductionmentioning
confidence: 99%